Genetic Evidence for Function of the bHLH-PAS Protein Gce/Met As a Juvenile Hormone Receptor - Jindra, Marek; Uhlirova, Mirka; Charles, Jean-Philippe; Smykal, Vlastimil; Hill, Ronald J (PLoS genetics, 2015)
Juvenile hormones (JHs) play a major role in controlling development and reproduction in insects and other arthropods. Synthetic JH-mimicking compounds such as methoprene are employed as potent insecticides against significant agricultural, household and disease vector pests. However, a receptor mediating effects of JH and its insecticidal mimics has long been the subject of controversy. The bHLH-PAS protein Methoprene-tolerant (Met), along with its Drosophila melanogaster paralog germ cell-expressed (Gce), has emerged as a prime JH receptor candidate, but critical evidence that this protein must bind JH to fulfill its role in normal insect development has been missing. Here, we show that Gce binds a native D. melanogaster JH, its precursor methyl farnesoate, and some synthetic JH mimics. Conditional on this ligand binding, Gce mediates JH-dependent gene expression and the hormone's vital role during development of the fly. Any one of three different single amino acid mutations in the ligand-binding pocket that prevent binding of JH to the protein block these functions. Only transgenic Gce capable of binding JH can restore sensitivity to JH mimics in D. melanogaster Met-null mutants and rescue viability in flies lacking both Gce and Met that would otherwise die at pupation. Similarly, the absence of Gce and Met can be compensated by expression of wild-type but not mutated transgenic D. melanogaster Met protein. This genetic evidence definitively establishes Gce/Met in a JH receptor role, thus resolving a long-standing question in arthropod biology.
Keywords: Protein Binding; transkripční faktory bHLH; Drosophila melanogaster; Drosophila Proteins; Juvenile Hormones; Cell Line; proteiny Drosophily; vývojová regulace genové exprese; Basic Helix-Loop-Helix Transcription Factors; Gene Expression Regulation, Developmental; signální transdukce; Signal Transduction; Animals, Genetically Modified; vazba proteinů; Animals; Fatty Acids, Unsaturated; Transcription Factors; transkripční faktory; zvířata; buněčné linie; geneticky modifikovaná zvířata; nenasycené mastné kyseliny; juvenilní hormony